Implikasi Hukum Pengabaian Reklamasi dan Tata Ruang pada PT Ratu Samban Mining - M. Alfami Syafultra; Vina Ayu Havivah; M. Alvin Sandjaya (CV. ITTC INDONESIA, 2025)
This article examines alleged legal violations by PT Ratu Samban Mining (PT RSM) in its coal-mining operations in Bengkulu Province. Key issues include non-compliance with reclamation obligations, the use of protected forest areas for mining activities, and suspected manipulation of coal-quality data that may cause state losses. Using a normative juridical method with statutory and conceptual approaches, the study evaluates the company’s actions in relation to the existing legal framework. The findings indicate weak corporate compliance, ineffective state oversight, and potential institutional maladministration. The gap between legal norms on environmental duties, forest protection, and accurate production reporting and actual field practices reveals structural problems in mining governance. If proven, PT RSM may face administrative, civil, and criminal liability. The study underscores the need for comprehensive governance reform, stronger supervision, greater transparency, and consistent law enforcement to ensure sustainable and accountable resource management.